The comparison of immunological responses of Brahman, Nguni and Angus cattle infested with Rhipicephalus microplus and Rhipicephalus decoloratus - Nel, Cornelius Loftus (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScAgric)--Stellenbosch University, 2017.